Elevated Plasma D-Dimer Levels Correlate with Long Term Survival of Gastric Cancer Patients - Liu, Long; Zhang, Xi; Yan, Bing; Gu, Qunhao; Zhang, Xiaodong; Jiao, Jianpeng; Sun, Dazhi; Wang, Ning; Yue, Xiaoqiang (PloS one, 2014)
Increasing evidence indicated plasma D-dimer could be regarded as a marker in cancers, however, its role in gastric cancer is still largely unknown. Plasma D-dimer levels were measured by enzyme linked fluorescent immunoassays and evaluated by receiver operating characteristic (ROC) curves for peritoneal dissemination in gastric cancer and healthy subjects. The overall survival (OS) characteristics were determined using Kaplan-Meier and Cox regression analyses. The average of the plasma D-dimer levels for gastric cancer patients was significantly higher than the healthy subjects. A Spearman correlation analysis showed that plasma D-dimer levels correlated with the depth of invasion, lymph node metastasis, peritoneal dissemination, distant metastasis, tumor size and TNM stage. The mean plasma D-dimer level was 2.20 ± 1.51 µg/mL in peritoneal dissemination patients and 1.01 ± 0.79 µg/mL in non-peritoneal dissemination patients (P<0.001). Additionally, the mean plasma D-dimer concentration in patients alive at the final follow-up evaluation was 0.79 ± 0.72 µg/mL,which was significantly lower than the amounts determined for the deceased patients (1.36 ± 1.13 µg/mL) (P<0.001). The AUC of D-dimer was 0.833 (95%CI: 0.780-0.885). At a cut-off value of 1.465 µg/mL, the D-dimer measurement had a sensitivity of 78.00%, a specificity of 83.76% and an accuracy of 82.59%. The median OS was 48.10 months (95% CI: 43.88-52.31) in patients with plasma D-dimer levels less than 1.465 µg/mL and 22.39 months (95% CI: 16.95-27.82) in patients with plasma D-dimer levels exceeding 1.465 µg/mL (log-rank test, P<0.001). Importantly, plasma D-dimer levels exceeding 1.465 µg/mL were significantly associated with poor OS, as determined using a multivariate Cox regression analysis (hazard ratio [HR], 2.28; 95%CI: 1.36-3.81; P = 0.002). Plasma D-dimer levels are increased in gastric cancer patients and may be a valuable biomarker for peritoneal dissemination, with high D-dimer levels predicting poor outcomes for gastric cancer patients.